PENGUKURAN KINERJA MELALUI PENDEKATAN BALANCED SCORECARD PADA PT. PLN (PERSERO) WILAYAH PAPUA CABANG MANOKWARI - Lili Sarce Joi Sapari (EKONOMI & SOSIAL, 2013)
The purpose of this study are: To determine the performance of PT. PLN (Persero) Branch Papua Manokwari area with  balanced scorecard approach. Type of research is descriptive-analytical type.       Results showed that 1) Performance of growing and learning with the concept of balanced scorecard has four (4) indicators of employee satisfaction, level of company information, employee turnover and employee productivity levels. From these indicators that need attention by PLN (Persero) Branch Papua Manokwari area for quality improvement is employee satisfaction "enough." Regional Branch Papua Manokwari need to increase the prosperity, harmony so that employees can create a dynamic working conditions and comfortable. 2) The performance of internal business process aspect of a balanced scorecard approach using indicators of innovation and progress. And has a process indicator score of "less".. This is caused by a lack of facilities and extent of the working area of PT. PLN (Persero) Branch Papua Manokwari District. 3) The performance of the customer aspect that reflects the company's ability to provide services and meet customer expectations for the desired level of service quality, measured by obtaining a balanced scorecard approach based on research results and data obtained by the score of "adequate "Highest Percentage but is" not satisfied "for the services of  PLN (Persero) Branch Papua Manokwari District. PT. Aspect customers is the aspect that most high level of sensitivity in shaping customer satisfaction even more PLN (Persero) Branch Papua Manokwari District is in the public service sector. With a score of "adequate" service PT. PLN (Persero) Wilayah Papua PLN (Persero) Regional Branch Papua Manokwari longer need achieve a score of "good".. And the point must be observed by the PT. PLN (Persero) Branch Papua Manokwari District is fulfilling its promise to customers. 4) In the perspective of the financial aspect, the balanced scorecard applied to help achieve financial tujuab, but at. PLN (Persero) Branch Papua Manokwari area of financial performance for the return on investment ratio is not optimal operation.